Implikatur Percakapan dalam Film “Hati Suhita” Adaptasi Novel Karya Khilma Anis - Shiva Arinda Putri Hardiasari; Yuni Sagita; Najla Fadhila; Tricya Githa Sulistyawati; Asep Purwo Yudi Utomo; Qurrota Ayu Neina; Rossi Galih Kesuma (Pusat Riset dan Inovasi Nasional, 2024)
The film “Hati Suhita” released in 2023 is an adaptation of the novel by Khilma Anis. Because it is set in an Islamic boarding school causes the film to have dialogues that are thick with politeness. However, this does not deny that the film also contains conversational implicatures. The aim of this study is to describe the forms of conversational implicatures found in the film “Hati Suhita” and explain how the process of violating the principle of cooperation and the principle of politeness can cause the emergence of implicatures. This study uses two approaches, namely a theoretical approach with pragmatic studies and a qualitative descriptive approach as a methodological approach. The data collection method uses the listening method with advanced techniques, namely the proficient free-involved listening technique and note-taking technique. Based on the 736 speech data from the film “Hati Suhita”, 63 speeches containing conversational implicature were found. The details of the implicature are 26 implicatures caused by the violation of cooperation principle and 37 implicatures caused by the violation of politeness principle. The thimble violation that creates the most implicature in the film is the violation of the thimble of agreement maxim. In addition, no violations of the thimble of modesty maxim and the thimble of obligation of S to O maxim were found in the analyzed data. Hopefully, this research can reveal the implied meanings in the dialogue between the characters in the film Hati Suhita.